How Accurate Are Value‐at‐Risk Models at Commercial Banks? - Berkowitz, Jeremy; O'Brien, James (Journal of Finance, 2002)
ABSTRACT In recent years, the trading accounts at large commercial banks have grown substantially and become progressively more diverse and complex. We provide descriptive statistics on the trading revenues from such activities and on the associated Value‐at‐Risk (VaR) forecasts internally estimated by banks. For a sample of large bank holding companies, we evaluate the performance of banks trading risk models by examining the statistical accuracy of the VaR forecasts. Although a substantial literature has examined the statistical and economic meaning of Value‐at‐Risk models, this article is the first to provide a detailed analysis of the performance of models actually in use.